Pattern of human resource development in Indian agricultural universities - JAIN, VANITA; PANDEY, P S; CHOUBEY, A K; MALHOTRA, KSHITIJ; MURTHY, G R K (The Indian Journal of Agricultural Sciences, 2022)
Agriculture is the primary sector of Indian economy contributing substantially towards GDP of the country. Qualified and quality human resources contribute significantly towards agricultural sector in the economy. The present study (2021) attempts to analyze the human resource development in terms of enrollment pattern of students in undergraduate (UG) course of agriculture and allied sciences and reflects on evolving strategies for attracting talented students in this sector. Present study shows that there is a close correlation with State Value of Output in agricultural sector and number of students enrolled in higher agricultural and allied studies. Presently, there are 74 agricultural universities (AUs) under the National Agricultural Research Education System and the present study attempts to analyze the student enrollment patterns of under-graduate students in agricultural universities of India for meeting the scientific manpower needs towards achieving targeted agricultural growth. Five years of enrollment data (2015–20) across AUs was considered. Human resource development in terms of enrolment in the higher agricultural education of agricultural universities is quite low when compared to enrolment of students overall in higher education and pattern of enrollment of girls varied in different regions of the country. This study has brought out an important aspect linked to higher agricultural education that the State Value of Output in agriculture has a positive association with enrollment of the students in higher agricultural education from the state in agricultural sector. It is important to assess the future human resource needs for the various sub-sectors of agriculture.